Accuracy of GPS device to asess rsa - Suárez, G.; Suarez-Arrones, L.; Urbano, R.; Nunez, F. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The accuracy of GPS devices to measure distance covered in team sports and their use as an alternative to photocells to evaluate sprint and RSA performance, has been described previously (Barbero-Alvarez et al., 2010; Coutts and Duffield, 2010). The purpose of the present study has been to determine the validility of the GPS device model (VX300) to asses performance in repeated sprint ability none lineal (Shuttle Sprint test). Methods: This study has been 30 physically active athletes. They did a RSA test with change of direction (Shuttle Sprint Test), times obtained using photocells and carrying the GPS device. The variables obtained by RSA test have been: the best time or the highest peak of velocity (RSAbest), the average time or average peaks of velocity (RSAmean) and the fatigue rate (RSAIFF). Results: Through the "RSA Test", using fotocell, the athletes obtained an average time of 7.33 s for the RSABest, a RSAMean of 7.81 s and a RSAIFF of 6.54. Using the GPS device, the RSABest was 26.09 km/h, a RSAMean of 23.94 km/h and a RSAIFF of -8.21. The correlations found between both devices being -0.81 in the RSABest, of -0.95 in RSAMean and of -0.38 in the RSAIFF. Discussion: The results of the study show that there exists a strong correlation between the times obtained through the photocells and the peak of speed reported by the GPS device. Similar results have been found in another study however carried out with different devices and distances (Barbero-Alvarez et al., 2010)